Factors affecting teachers’ behaviour in work innovation - Abel, Raj Sethupathy (2019)
This study is about teacher responses to the implementation of School Based Assessment (SBA) in Kuala Langat secondary schools. Organizational research on Employee Silence described that individuals hold back their opinions regarding work issues due to various reasons. Although much of the studies concerning Employee Silence was done outside the education field, the main objective in this study is to examine if teachers too have the tendency to adopt similar behavior when faced with issues in the Work Innovation (SBA). Employee Silence research indicate that the danger of such a behavior can escalate into total dissatisfaction at the workplace due to prolonged unhappiness. This research design utilized a quantitative approach, using a survey instrument. Survey items were modified from previous research to suit the objectives of this study. Reliability and Validity tests were conducted with no issues in the outcome. The reliability test produced an average alpha value of > 0.70. Following that, the actual study was carried out on 320 teachers, identified using the simple random sampling method. The instruments were personally distributed and collected by the researcher. The analysis of data was carried out using Descriptive and Inferential Statistics. The findings indicated that teachers too have a tendency to adopt the Silence approach when faced with SBA issues in their respective schools. This is consistent with research findings in business organizations whereby such a behavior is a deliberate choice of action to hold back workplace information from the management. The significance of this study is to emphasize the importance of upward communication in the form of feedback, which is important for schools to achieve top performance. Effective teacher-management communication can create a conducive environment which motivates all individuals. Policy makers at the Ministry of Education Malaysia too can benefit by considering the outcome of this study to further refine the SBA so that the issues and problems faced by teachers will be given due attention. In conclusion, all parties concerned need to strive to create a conducive environment at schools so that a free flow of communication becomes a culture among all individuals in the organization. As such, principals, and top management must create a climate to tap the best from teachers through frequent and effective two-way communication.